ANALISIS TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM PADA PT. INDOCEMENT TUNGGAL PRAKARSA, TBK - Rahmawati; Nafisah Nurulrahmatiah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine and analyze Total Asset Turnover Against Stock Prices at PT. Indocement Tunggal Prakarsa, Tbk therefore this research will be of associative type. The instrument is a list of tables which contain data components on total assets, sales and stock prices. The research data has a population of 23 years with a sample of the financial statements of PT. Indocement Tunggal Prakarsa, Tbk for 10 years, from 2012 to 2021 using a purposive sampling technique. The data collection technique used in this research is documentation and literature study. Processing the data with the help of the SPSS program and then analyzing the data with linear regression analysis techniques, correlation coefficients, the t test of determination and finally the f test. The results showed that there was no significant effect between Total Asset Turnover on Stock Prices at PT. Indocement Tunggal Prakarsa, Tbk.